2019
DOI: 10.1177/0885066619870153
|View full text |Cite
|
Sign up to set email alerts
|

Early Tracheostomy for Severe Pediatric Traumatic Brain Injury is Associated with Reduced Intensive Care Unit Length of Stay and Total Ventilator Days

Abstract: Objectives: To determine whether, similar to adults, early tracheostomy in pediatric patients with severe traumatic brain injury (TBI) improves inhospital outcomes including ventilator days, intensive care unit (ICU) length of stay (LOS), and total hospital LOS when compared to late tracheostomy. Design: Retrospective cohort analysis. Setting: The Pediatric Trauma Quality Improvement Program (TQIP) database Patients: One hundred twenty-seven pediatric patients <16 years old with severe (>3) abbreviated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The search did not return any randomized trials. The authors found eight studies 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 that compared the prognoses of patients undergoing “early” or “late” tracheostomy: in five, “early tracheostomy” was defined as being performed before 14 days of mechanical ventilation, and “late,” after this period. In two studies, “early” was defined as before seven days post-trauma injury, and, in one, as before ten days of ventilation ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The search did not return any randomized trials. The authors found eight studies 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 that compared the prognoses of patients undergoing “early” or “late” tracheostomy: in five, “early tracheostomy” was defined as being performed before 14 days of mechanical ventilation, and “late,” after this period. In two studies, “early” was defined as before seven days post-trauma injury, and, in one, as before ten days of ventilation ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…– 18 y. < 7 days post-trauma 43/48 Death in hospital 14 (9.7) 21 (10.3) 7 Sheehan et al, 2019 64 Retrospective cohort Traumatic brain injury patients, <16 y. < 7 days post-trauma 16/111 Death in hospital 9.7 (6.5) 27.1 (28.9) 7 McLaughlin et al, 2019 65 Retrospective, propensity score matching Children with severe traumatic brain injury, <15 years ≤ 14 days of MV 121/121 Death in hospital 14 (7.4) 26 (11.8) 9 Pizza et al, 2017 66 Retrospective cohort General PICU Age range: 0 y.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations